3(x-6)+8=5(x+2-6

Simple and best practice solution for 3(x-6)+8=5(x+2-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-6)+8=5(x+2-6 equation:



3(x-6)+8=5(x+2-6
We move all terms to the left:
3(x-6)+8-(5(x+2-6)=0
We add all the numbers together, and all the variables
3(x-6)-(5(x-4)+8=0
We multiply parentheses
3x-(5(x-4)+8-18=0

See similar equations:

| 2x−10|=−3x | | -6+x.25=-5 | | .5^x=1.3 | | 10m+3=12-8m | | 3=4k | | -6=n.50-10 | | 5w^2+30w-80=0 | | 0.8k+6=0.2k-10 | | 2x•x=360 | | 10z-z=-3+2z-1-10 | | 3(-z+6)+2=-18 | | 3a2+11a-4=0 | | 4x+5+6x-2=24 | | -4=r.20-5 | | 10m+3=12+8m | | (x+3)*(x+4)=(x+1)*(x+2) | | -25-7m=6(4m+1) | | 31=-7n | | -4/p=12 | | 1/3=1/4+f | | 2x2+9=-41 | | .5^z=1.3 | | 63=x+3x+5x | | 5/9y+26=-6 | | 9/5+3/5x=31/15+8/3x+1/3 | | 11(b+7)=40 | | -2=2+v.25 | | 39/x=35/100 | | (x-1)*(x+7)=(x+1)*(x-3) | | -34=-61-9f | | 6(2+6r)-6=-66 | | b-(-16)=0 |

Equations solver categories